PENGARUH PENGALAMAN KONSUMEN DAN NILAI KONSUMEN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN - Syafa'atun Munajah (2021)
This quantitative research was conducted to examine the influence of consumer experience and consumer value on consumer loyalty through consumer satisfaction by using a sample of 100 respondents through purposive sampling method. The data was collected using a questionnaire via a google form which was distributed to the 2018-2021 FEB UPN Veteran Jakarta Undergraduate Program Students. In data analysis using Partial Least Square software. With the test results obtained, namely (1) consumer experience does not have a significant influence on consumer loyalty. (2) Consumer value has a significant influence on consumer loyalty. (3) Consumer satisfaction has a significant influence on consumer loyalty. (4) Consumer experience has no influence on consumer loyalty through customer satisfaction. (5) Consumer value has no influence on consumer loyalty through customer satisfaction.